Ecoepidemiología de la estomatitis vesicular en un municipio cafetero de Antioquia (2001)
ABSTRACT: The prevalence of Vesicular Stomatitis Virus, VSV, in sentinels herds, wild reservoirs and vectors in two dairy farms in the Fredonia town, (Antioquia, Colombia), was determined. Blood serum samples from cows and wild reservoirs were tested by neutralization test, viral isolation from vectors and reservoirs; vectors macerated and blood from wild reservoirs were tested by RT-PCR and Nested-PCR to identify viral genome fragments. The percentage of domestic animals in the farms, with antibodies against VSV IN was 57.14% whereas 73.01% of the animals had antibodies against VSV NJ. On the other hand, in wild animals we found that 37.5% of them had low titer of antibodies, 1:8 principally, against VSV IN only, for this reason is suggested that domestic and wild cycle of the VSV don’t have any relationship. All blood samples from reservoirs and vectors tested by RT-PCR and Nested PCR, were negative for the both serotypes. In this paper we discuss the results and we suggest the realization of additional studies regarding this aspects.